Applications of Cognitive Psychology to Mathematics Education - Zhanjiang Zhi, Dongliang Xu (Forest Chemicals Review)
In the context of the reform of mathematics curriculum teaching in middle schools, how to continuously improve the quality of mathematics classroom teaching has become an important issue. Combining the relevant theories of cognitive structure in mathematical educational psychology and the practical experience in the teaching process, this paper explores how to optimize teaching strategies under the support of educational psychology theory from three aspects: cognitive connection, mathematical understanding and emotional factors, and truly realize the mathematics quality education about the human subject.